DEVELOPMENT OF VIDEO MEDIA TUTORIAL LEARNING TO IMPROVE LEARNING CONCENTRATION AND ACHIEVEMENT (Study on Digital Photo Composition Subjects of Vocational Multimedia Programs in Bengkulu) - Marlina Marlina; Alexon Alexon (DIADIK, 2018)
The purpose of this study to develop and use tutorial learning video media that was implemented using the Camtasia Software to improve student concentration and learning achievement, especially in the Digital Photo Composition subject in the Multimedia department in Bengkulu and to test the effectiveness of the media. The subjects of this study were teachers and students at the SMKS 4 PGRI Kota Bengkulu, SMKS 1 Pembangunan Kota Bengkulu, dan SMKN 1 Kota Bengkulu.  This research method is Research and Development (R & D) which is implemented in three steps: Development Model, Development Procedure, and Product Trial. The results of this study are developing and using learning video media with the Camtasia Software to accommodate visual, audio, and animation, and the results of this study prove that learning video media that are developed and very effective in improving students' achievement and learning concentration.